Detection of Early Pneumonia on Individual CT Scans with Dilated Convolutions - Радюк, Павло Михайлович; Radiuk, P. M.; Krak, Iurii; Barmak, Olexander (My University, 2021)
Over the past decades, pneumonia has been considered one of the most dangerous diseases, leading to severe consequences in a short time. Without proper and timely treatment, pneumonia can lead to fatal consequences. Thus, early diagnosis and detection of this lung disease are crucial in successful treatment and constant monitoring. Indeed, there is a high demand for the development of medical image technologies for disease identification. In this paper, we propose a novel information technology for robust feature identification and early detection of pneumonia on computer tomography scans. We also propose a new modified convolutional neural network as a core feature extractor. An effective dilated convolution operation with different rates, combining features of various receptive fields, was utilized to detect and analyze visual deviations in targeted images. Due to applying the dilated convolutions, the network avoids significant losses of objects' spatial information while providing low computational losses. The investigated model classifies computed tomography images with a validation accuracy of up to 96.12%. Overall, our approach requires much fewer computing resources, proving its effectiveness for solving practical problems on available computing devices.
Krak Iu., Barmak O., Radiuk P. Detection of Early Pneumonia on Individual CT Scans with Dilated Convolutions / Iu. Krak, O. Barmak, P. Radiuk // CEUR-Workshop Proceedings. – 2021. – Vol. 2853. – P. 214-227.
Keywords: Pneumonia detection; computer tomography; feature extraction; deep learning; convolutional neural network; dilated convolution; individual approach; Research Subject Categories::TECHNOLOGY